BiOBr/NiO S‐Scheme Heterojunction Photocatalyst for CO2 Photoreduction. Issue 1 (24th August 2021) - Wang, Zhongliao; Cheng, Bei; Zhang, Liuyang; Yu, Jiaguo; Tan, Haiyan
Abstract : Artificial photosynthesis by CO2 photoreduction is an ideal channel for mitigating the greenhouse effect and energy crises. Nevertheless, its efficiency is still low due to severe charge recombination and sluggish kinetics. Herein, an S‐scheme BiOBr/NiO heterojunction, composed of two kinds of p‐type semiconductors, exhibits enhanced CO2 photoreduction activity. Enhanced light absorption and specific surface area are attributable to NiO nanosheets with hierarchical porous structures. Results from in situ irradiated X‐ray photoelectron spectroscopy and work function calculation manifest that the photoexcited electrons transfer from BiOBr to NiO via the S‐scheme mechanism. And charge separation and a strong redox ability are simultaneously realized. In situ diffuse reflectance infrared Fourier transform spectra unveil complex intermediates in CO2 photoreduction. This work presents a novel understanding for the CO2 photoreduction mechanism of S‐scheme heterojunctions built by p‐type semiconductors by integrating in situ monitoring techniques with density functional theory calculation. Abstract : Benefited from ameliorated charge separation, strong redox ability of S‐scheme heterojunction and excellent CO2 photoreduction for BiOBr/NiO composites are accomplished. The CH4 and CO yielding rates for optimized BN15 reach 6.6 and 12.8 μmol g −1  h −1, higher than that of pristine BiOBr (0.8 and 3.4 μmol g −1  h −1 ) and NiO (4.3 and 4.4 μmol g −1  h −1 ).